Family money property, race, and literature in the nineteenth century - Clymer, Jeffory A. (New York ; Oxford : Oxford University Press, 2013)
Combining nuanced literary interpretations with significant legal cases, 'Family Money' reveals a shared preoccupation with the financial quandaries emerging from interracial sexuality in nineteenth-century America. At stake, Clymer shows, were the very notions of family and the long-term distribution of wealth in the United States.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: American literature -- 19th century -- History and criticism; Miscegenation in literature; Intimacy (Psychology) in literature; Literature and society -- United States -- History -- 19th century; Interracial marriage -- United States